Efficacy of intravenous dexmedetomidine versus intraperitoneal dexmedetomidine in laparoscopic cholecystectomy – A prospective randomized double-blinded study - Kandi, Sumati; Panigraghy, Laxmi Kanta; Dhamudia, Harish chandra; Patel, Pradipta Kumar; Sethi, Panchanana (Asian Journal of Medical Sciences, 2022)
Background: Dexmedetomidine now has become one of the frequently used drugs as part of a multimodal analgesic regimen to provide improved pain control at all perioperative stages for laparoscopic surgeries. Aims and Objectives: In this prospective, double-blind, randomized, and control trial, we compared the postoperative analgesic efficacy of intravenous (IV) dexmedetomidine and intraperitoneal (IP) dexmedetomidine in laparoscopic cholecystectomy. Materials and Methods: Sixty patients of the American Society of Anesthesiologists Grade I and II undergoing laparoscopic cholecystectomy were allocated into two groups. The patients in Group-IV had received 30 ml of 0.5 μg/kg Dexmedetomidine infusion intravenously plus 40 ml of Ropivacaine (30 mL of 0.5% Ropivacaine and 10 ml NS) intraperitoneally and in Group-IP received 30 ml NS intravenously and 40 ml of Ropivacaine plus Dexmedetomidine (30 mL of 0.5% Ropivacaine and 0.5 μg/kg Dexmedetomidine diluted in 10 ml NS) intraperitoneally after removal of the gallbladder. Patients were assessed during the first 24 h postoperatively for time to the first requirement of analgesia, total analgesic consumption, sedation, hemodynamics, side effects, and patient satisfaction. Results: Time to first request of analgesia (min) was longer (216.46±42.19 vs. 108.03±48.77) and total analgesic consumption (mg) was lower (92.50±32.26 vs 115.0±38.056) in Group-IV than in Group-IP. A significant difference was observed in visual analogue score in Group-IV at 1 h, 2 h, 4 h postoperatively and in the patient satisfaction score (P=0.024) in comparison to Group-IP. Conclusion: The postoperative analgesic effects and patient satisfaction, of low dose IV Dexmedetomidine plus IP instillation of Ropivacaine, are superior to low dose IP Dexmedetomidine added to Ropivacaine.